Development of New Methods and Materials for the Restoration of Tooth Pulp - Terekhov, Serhii; Pasichnyk, Maryana; Proshchenko, Andrii; Proshchenko, Nina; Kasіanenko, Dmytro (International Journal of Statistics in Medical Research, 2024)
Nowadays, the latest treatment technologies are actively developing in dental practice, namely for the restoration of tooth pulp. Aim: to evaluate the advantages of using modern materials in the treatment of tooth pulps. Materials and Methods: We examined 33 patients with pulp diseases: 18 women (54.5%) and 15 men (45.5%) with an average age of (33.2±2.3) years. 18 patients (group I) had conservative treatment; 15 patients (group II) got pulp restoration using Biodentin. Results: In 33 (100 %) patients of both groups, inflammation of tooth pulps was found; in 5 of 18 (27.8 %) patients of group I and 6 of 15 (40.0 %) patients of group II, the presence of fibrous pulpitis without signs of periodontitis was determined, in patients of group II, 4 of 15 (26.7 %) - acute diffuse pulpitis. Streptococci with α-haemolytic activity, staphylococci and fungi of the genus Candida albicans were detected in the plaque. In 93.3% of patients, both clinical and overall success was achieved with Biodentin, and the frequency of isolation of microorganisms of the genus Streptococcus spp. with α-haemolytic activity and Candida albicans decreased. Conclusions: Effective pulp restoration, inflammatory process reduction, and conditionally pathogenic microflora suppression were found in patients treated with Biodentin.